2020
DOI: 10.3892/ol.2020.11382
|View full text |Cite
|
Sign up to set email alerts
|

Methylation profiling in promoter sequences of ATM and CDKN2A (p14ARF/p16INK4a) genes in blood and cfDNA from women with impalpable breast lesions

Abstract: The objective of the present study was to evaluate the epigenetic changes occurring in early stages of breast cancer. The present study investigated the methylation profile of the ATM, p14 ARF and p16 INK4a promoters in total blood and plasma cell-free DNA (cfDNA) from women with impalpable breast lesions compared with in total blood of a control cohort of women without breast lesions. The samples were evaluated using the methylation-specific PCR method. The Fisher's exact test was used to evaluate statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A small number of studies have explored the Oncomine cfDNA Assay in breast cancer; one was limited to advanced disease, 28 whereas another was used to determine whether mutations could be identified in cfDNA from serum stored for 30 years. 29 We also investigated the prevalence of CHIP-derived mutations in ctDNA, normal hemopoietic cells accumulating somatic mutations during the aging process in the absence of cancer. 14 Such mutations can potentially arise in highly sensitive next-generation sequencing data because of inaccurate variant calling, sequencing artifacts, and somatic tumor-relevant SNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of studies have explored the Oncomine cfDNA Assay in breast cancer; one was limited to advanced disease, 28 whereas another was used to determine whether mutations could be identified in cfDNA from serum stored for 30 years. 29 We also investigated the prevalence of CHIP-derived mutations in ctDNA, normal hemopoietic cells accumulating somatic mutations during the aging process in the absence of cancer. 14 Such mutations can potentially arise in highly sensitive next-generation sequencing data because of inaccurate variant calling, sequencing artifacts, and somatic tumor-relevant SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Since the inception of this study, several groups have reported different assays potentially capable of helping in the differential diagnosis of breast diseases, and thus are candidate blood tests for use as a part of a screening strategy. These include DNA methylation analysis, 29 ctDNA fragmentation assays, 22 and a multianalyte platform. 23 Our results show that screening with the assay could be used in combination with other such strategies, and future studies could focus on developing technologies to improve sensitivity, determining the added value of measuring other analytes, 23 and the application of machine learning 22 in improving diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common cancer associated with high mortality rates among women worldwide [3]. The silencing of tumor suppressor genes by hypermethylation is an essential epigenetic mechanism in breast tumorigenesis [20]. Epigenetic alterations differ from genetic ones primarily in their greater frequency, incomplete reversibility, and their location in fixed genome regions.…”
Section: Discussionmentioning
confidence: 99%
“…Delmonico et al investigated plasma cfDNA from women with and without impalpable breast lesions to detect the epigenetic alterations and observed that ATM and p14 ARF showed higher methylation rates in samples from women with malignant lesions and older than 50 years. 38 Thus, the authors described the potential detection of epigenetic changes in liquid biopsy to monitor the impalpable breast lesions.…”
Section: Methylation Signature In Cfdnamentioning
confidence: 99%